2011
DOI: 10.1007/s00261-011-9828-4
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome of percutaneous radiofrequency ablation in renal cell carcinoma: a retrospective study of intraoperative contrast-enhanced ultrasonography in 73 patients

Abstract: Intraoperative CEUS can "real-time" monitor the ablated area during PRFA procedure. This technique can help to achieve a higher success rate compared with conventional ultrasound. No impact of intraoperative CEUS has been found on GFR level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
2
22
0
2
Order By: Relevance
“…Moreover CEUS allows a "real-time" monitorization of the ablated area during RFA procedure which may provide a higher success rate than in the case of US monitoring [17]. These results were confirmed by another study where CEUS was superior to clasic US monitoring in achieving the local tumour control (100 % vs.87.5%).…”
Section: Monitoring Of Renal Lesions Treated By Percutaneous Ablationsupporting
confidence: 77%
“…Moreover CEUS allows a "real-time" monitorization of the ablated area during RFA procedure which may provide a higher success rate than in the case of US monitoring [17]. These results were confirmed by another study where CEUS was superior to clasic US monitoring in achieving the local tumour control (100 % vs.87.5%).…”
Section: Monitoring Of Renal Lesions Treated By Percutaneous Ablationsupporting
confidence: 77%
“…The reported sensitivity and specificity of CEUS for the evaluation of residual or recurrent RCC are 82.2-100%, and 96.6-100% [39,40,43,44], respectively, with an accuracy of 90.5-98.1% [39,40,43]. The concordance of CEUS with CECT or CEMRI ranges between 80 and 100% [38][39][40][41][42].…”
Section: Ceus and Follow-upmentioning
confidence: 93%
“…Conversely, CEUS may be more sensitive in the detection of small ablation-related complications, such as kidney hematoma and perirenal effusion [39,40]. Several studies have assessed the use of CEUS from one day to one week after ablation of RCC, and report a high sensitivity, specificity and accuracy for early detection of residual unablated tumor tissue, comparable to CECT and CEMRI [38][39][40][41][42]. 6.…”
Section: Intraprocedures Evaluationmentioning
confidence: 95%
“…A meta-analysis including 11 studies showed promising results for using CEUS to distinguish benign and malignant lesions with a pooled sensitivity of 0.88 (95% CI: 0.85À 0.90), pooled specificity of 0.80 (95% CI: 0.75À0.85), and receiver-operator characteristic area under the curve of 0.922 [10]. Ongoing developments for CEUS or Doppler imaging and comparative studies show promising results [6,[8][9][10][11][12][13]. However, in many countries, including the United States, microbubbles are not approved for use in the abdomen and therefore its use has been very limited.…”
Section: Introductionmentioning
confidence: 99%